New consultants mastering the role of on‐call supervisor: a longitudinal qualitative study. Issue 4 (12th March 2013) - Westerman, Michiel; Teunissen, Pim W; Fokkema, Joanne P I; Siegert, Carl E H; van der Vleuten, Cees P M; Scherpbier, Albert J J A; Scheele, Fedde
Abstract : Context The supervision of specialty registrars during on‐call shifts is essential to ensure the quality of both health care and medical education, but has been identified as a major novelty and stressor for new consultants in the transition from specialty training. There is a paucity of research on how consultants deal with their new supervisory roles and which factors influence this process. These issues are addressed in a prospective study designed to gather insights that can inform measures to ensure the provision of high‐quality supervision and specialty training. Methods A longitudinal qualitative study was performed in the Netherlands. Semi‐structured interviews were conducted with new consultants. The study was guided by an interpretative phenomenological approach until saturation was reached. At 3‐month intervals between July 2011 and March 2012, eight novice consultants in internal medicine were interviewed three times each about their supervisory role while on call. Interviews focused on their preparation for the role in training, the actions they took to master the role, and their progression over time. Results Three interrelated domains of relevant factors emerged from the data: preparedness; personal characteristics, and contextual characteristics. Preparedness referred to the extent to which new consultants were prepared by training to take full responsibility for registrars' actions while supervising them from a distance. Personal characteristics, such as coping strategies and views on supervision, guided consultants' development as supervisors. Essential to this process were contextual characteristics, especially those concerning the extent to which the consultant knew the registrar, was familiar with departmental procedures, and had access to support from colleagues. Conclusions New consultants should be prepared for their supervisory role by training and by being given a proper introduction to their workplace. The former requires progressive independence and exposure to supervisory tasks during specialty training; the latter requires an induction programme to enable new consultants to familiarise themselves with the departmental environment and the registrars they will be supervising. Abstract : Discuss ideas arising from this article at http://www.mededuc.com'discuss'